Investigation of graphene gas sensor at different substrates for acetone detection - Mohd Chachuli, Siti Amaniah; Yap, Pei Yeuan; Coban, Omer; Shamsudin, Nur Hazahsha; Idris, Muhammad Idzdihar (Wydawnictwo SIGMA-NOT, 2023)
Acetone gas is a colorless and flammable gas. Hence, it is one of the primary sources that causes combustion in high-temperature conditions. Besides, it is harmful to the health of living things. It will induce dizziness, headaches, vomiting, and irritation to the nose, eye, and throat in the short term. In the long term, it will cause damage to the central nervous system, cancer, liver, and kidney. This project aims to develop a graphene gas sensor to sense acetone and investigate the performance of the fabricated gas sensors at various thicknesses on different substrates. The substrates used are glass and Kapton film. 10 g of DI water was mixed with three different weights of graphene powder (0.01 g, 0.02 g, and 0.05 g) using a sonication bath for 30 minutes. The thickness of the sensing layer was varied through different amounts of graphene powder used in the solutions. Initially, the interdigitated electrode was deposited onto the substrates using screen-printing and annealed at 150 for 10 minutes. After that, the sensing layer was deposited on the interdigitated electrode using the dropping technique by dropping one drop of the mixed solution and annealing at 150 for 10 minutes. SEM and XRD characterizations are carried out to verify the sensing material of the gas sensor. The results revealed that gas sensors prepared by 0.01 g of graphene and 10 g of DI water (D-1b and D1b) produced high sensitivity to acetone compared to other samples. The gas sensor on Kapton film (D1b) had higher sensitivity than the gas sensor on the glass substrate (D-1b), with sensitivity values of approximately 7.02% and 3.24%, respectively. Sample D-2b has the shortest response time (4 s), while sample D-5b has the fastest recovery time (5 s) to acetone vapor.